The Impact of Social Media Marketing on Jenius - Lambert, Joseph; Vanderssen, Felix; Sanjaya, Christnaldy; Yulianto, Yulianto (APPS Publications, 2024)
Objective – The aim of the study is to investigate the influence of social media marketing activities on the development of brand love for the Jenius digital banking brand among its target audience. Methodology – This study employs a quantitative research approach, likely using surveys or analyzing digital engagement metrics, to examine the relationship between specific social media marketing activities of Jenius and the level of brand love experienced by its consumers. Statistical analysis will be used to determine the strength and direction of this influence. Findings – The findings of this study would likely demonstrate a statistically significant positive relationship between specific social media marketing activities employed by Jenius (such as engaging content and WOM campaigns) and the level of brand love experienced by its consumers. This suggests that Jenius's social media strategies are effective in fostering emotional attachment and positive feelings towards the brand. Novelty – The novelty of this study lies in its specific examination of how social media marketing cultivates brand love within the unique context of a digital banking brand (Jenius) and its Indonesian consumer base.